2000
DOI: 10.1016/s0022-5347(05)67799-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Valrubicin for the Treatment of Bacillus Calmette-Guerin Refractory Carcinoma in Situ of the Bladder

Abstract: Valrubicin was effective and well tolerated in patients with carcinoma in situ of the bladder refractory to BCG therapy. Delaying cystectomy while attempting salvage therapy with valrubicin does not pose an undue risk to most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
124
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(135 citation statements)
references
References 14 publications
1
124
0
1
Order By: Relevance
“…Consequently, in 2013, Dinney et al provided an updated report on the safety and efficacy of valrubicin based on the revised phase III trial data along with data from a supportive phase II/III trial (A9303 trial). Based on the updates to the data originally reported in Steinberg, et al, 153 the complete response rate changed from 21% to 18%, which is identical to the CR reported in the supportive A9303 trial by Dinney et al 154 The supportive trial also demonstrated a disease-free status of 22% at six months, 10% at one year, and 4% at two years. 154 Because patients in the A9303 trial were less highly treated than in the previous phase III trial, Dinney et al conclude that valrubicin is both safe and efficacious in highly pretreated populations as well as those with few previous therapies.…”
Section: Current State Of the Fieldsupporting
confidence: 62%
See 1 more Smart Citation
“…Consequently, in 2013, Dinney et al provided an updated report on the safety and efficacy of valrubicin based on the revised phase III trial data along with data from a supportive phase II/III trial (A9303 trial). Based on the updates to the data originally reported in Steinberg, et al, 153 the complete response rate changed from 21% to 18%, which is identical to the CR reported in the supportive A9303 trial by Dinney et al 154 The supportive trial also demonstrated a disease-free status of 22% at six months, 10% at one year, and 4% at two years. 154 Because patients in the A9303 trial were less highly treated than in the previous phase III trial, Dinney et al conclude that valrubicin is both safe and efficacious in highly pretreated populations as well as those with few previous therapies.…”
Section: Current State Of the Fieldsupporting
confidence: 62%
“…Findings demonstrated that six weekly instillations of 800mg of valrubicin was well-tolerated and that 21% of patients remained disease-free six months after treatment, and responses were durable, with a median response time greater than 18 months. 153 These data were subsequently revised but only reported in the FDA prescribing information. Consequently, in 2013, Dinney et al provided an updated report on the safety and efficacy of valrubicin based on the revised phase III trial data along with data from a supportive phase II/III trial (A9303 trial).…”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…For post-BCG tumor recurrences, BCG-unresponsive disease is defined by any of the following features: recurrent NMIUC after 2 prior adequate BCG regimens, recurrent T1 disease at the initial 3-month post-treatment TURBT, recurrent NMIUC within 6 months of last BCG administration, and NMIUC involving the prostatic urethra (8). Transient remissions are often observed with additional intravesical therapy approaches, however, only 10-15% of patients remain recurrence-free at 1 year (9, 10). Thus, cystectomy is considered a standard treatment in BCG-unresponsive patients (11).…”
Section: Introductionmentioning
confidence: 99%
“…This poses a serious dilemma, especially in those who refuse radical cystectomy or have too many comorbidities to undergo a major operation. While other therapies such as mitomycin C are considered in this unique setting, the only Food and Drug Administration (FDA) approved intravesical option for BCG “failure” is valrubicin, which exhibits a modest response rate of 21% at 6 months [10]. …”
Section: Introductionmentioning
confidence: 99%